2020
DOI: 10.18257/raccefyn.1023
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la variación temporal de los parámetros hidráulicos en la estructura y la función de la comunidad de macroinvertebrados en un río andino

Abstract: En este estudio se evaluó la respuesta de la composición, la estructura y la función de la comunidad de macroinvertebrados a la variación temporal hidráulica en el río Agua Blanca. Se recolectaron 60 muestras en dos tramos durante dos épocas hidroclimáticas mediante un muestreo aleatorio estratificado. Se midió el caudal y el ancho del canal, así como la velocidad, la profundidad y elnúmero de Froude (Fr) en cada muestra biológica. En la prueba de Kolmogorov-Smirnov se evidenció un incremento significativo en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(52 reference statements)
0
1
0
2
Order By: Relevance
“…For example, Castella et al (2001) identified water temperature as the main driver of macroinvertebrate richness and community composition in glacier‐fed streams, and Petts and Bickerton (1994) reported that turbidity is generally unfavourable for macroinvertebrates. Motta‐Díaz and Vimos‐Lojano (2020) also showed that hydraulic characteristics at the stream reach scale (bed shear stress, flow velocity, and water depth) had a significant effect on macroinvertebrate community composition, with higher abundance of Simuliidae (Diptera) in deep habitats. Finally, the hydrological regime of alpine streams also represents a key proximate habitat variable to explain community composition, as it influences the quality and quantity of habitats available for aquatic organisms over time (Meißner et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…For example, Castella et al (2001) identified water temperature as the main driver of macroinvertebrate richness and community composition in glacier‐fed streams, and Petts and Bickerton (1994) reported that turbidity is generally unfavourable for macroinvertebrates. Motta‐Díaz and Vimos‐Lojano (2020) also showed that hydraulic characteristics at the stream reach scale (bed shear stress, flow velocity, and water depth) had a significant effect on macroinvertebrate community composition, with higher abundance of Simuliidae (Diptera) in deep habitats. Finally, the hydrological regime of alpine streams also represents a key proximate habitat variable to explain community composition, as it influences the quality and quantity of habitats available for aquatic organisms over time (Meißner et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…En general, la mayor abundancia fue para los órdenes Diptera, Ephemeroptera, Coleoptera y Trichoptera, siendo este último más abundante en época seca. Estos resultados son habituales en los sistemas fluviales de montañas de los Andes (Domínguez y Fernandez, 2009;Motta-Díaz y Vimos-Lojano, 2020). La familia más abundante en las dos épocas fue Chironomidae, lo que refleja su gran plasticidad ecológica.…”
Section: Composición De La Comunidad De Macroinvertebradosunclassified
“…Los macroinvertebrados no solo responden a las condiciones de calidad de agua, también son afectados por los cambios en el régimen de flujo, que, a su vez, modifica la estabilidad del lecho de forma diferente en cada mesohábitat y en las diferentes épocas hidrológicas, más aún cuando se trata de ecosistemas sometidos a escenarios de regulación. De manera que, los cambios de profundidad, velocidad y arrastre de sedimentos afectan la variedad y estabilidad de mesohábitat favorables para el establecimiento de estos organismos (Motta-Díaz & Vimos-Lojano, 2020;Walteros-Rodríguez & Castaño-Rojas, 2020).…”
Section: Introductionunclassified